Exploring microbial dynamics in ferruginous caves: taxonomic and functional diversity across seasons and cave zones - Bitencourt, José Augusto Pires; Bandeira, Débora Marina; Gonçalves, Affonso Celso; Snak, Aline; de Castro, Danielly Cristina Marques; de Lima Ribeiro, Rafaela; Argolo, Leandro Araujo; dos Santos Scherer, Rafael; Lima, Brenda Almeida; Albino, Ulisses Brigatto; Pinto, Fabiana Gisele da Silva (Frontiers in Microbiology, 2025)
Bacterial communities in ferruginous caves are known for their high diversity and functional adaptability to environmental conditions. In this study, we characterized the taxonomic and potential functional profiles of two iron-rich caves, GEM-1423 and GEM-1462, across photic, dysphotic, and aphotic zones during both rainy and dry seasons. High-throughput sequencing revealed distinct microbial community structures. GEM-1423 showed strong dominance of specific taxa, while GEM-1462 exhibited lower dominance of iron-metabolizing groups and higher beta diversity, particularly in the dry season—indicating a greater degree of species replacement. Notably, iron availability emerged as a key factor influencing microbial dynamics in both caves, affecting community composition and functional pathways. Core genera, such as Bacillus, Acidothermus, Mycobacterium, and Acidisphaera, were associated with nitrogen and carbon cycling, as well as indirect iron solubilization through production of organic acids. Potential functional profiles varied seasonally: energy metabolism was enriched during the dry season, while nutrient cycling pathways were more abundant in the rainy season. We also detected taxa involved in manganese oxidation, urea degradation, and functions with biotechnological relevance, including antimicrobial compound production and metal resistance. These findings highlight the complex interactions between environmental factors, microbial diversity, and ecosystem function in ferruginous caves, and underscore the biotechnological potential of microbial communities from extreme environments.